Relationships of Ex-vivo drug resistance assay and cytokine production with clinicopathological features in the primary cell culture of Thai Ovarian and Fallopian tube cancer patients - May Thuu Mon (2018)
Objective: Our goal was to determine the ex-vivo drug resistance assay, as well as the cytokine production, in response to platinum-based chemotherapy treatment in primary culture cells established from the tumor tissue of ovarian or fallopian tube carcinoma patients, and to predict the clinical responses to chemotherapy. Methods: Sensitivity to the platinum-based drug was analyzed in two ovarian cancer cell lines and 19 tumor samples using the primary cell culture obtained from 19 patients having ovarian or fallopian tube cancer that had undergone surgery from 2014 to 2017. Results: Our findings in the ovarian cancer cell lines showed that SKOV3 cells displayed 10-fold greater resistance to cisplatin and 5.8 times more resistance to carboplatin than A2780 cells. SKOV3 cells displayed platinum-induced IL-6 and IL-8 overproduction whereas wild type A2780 displayed no detectable cytokine production. Regarding the primary cell culture obtained from patients, ex-vivo drug resistance assay results revealed that although extreme drug resistance was correlated with late stage ovarian cancer (P= 0.031), it could not independently predict or alter the outcomes of patients with ovarian or fallopian tube cancer. No relationship was found between basal cytokine secretion and the clinical parameters. However, carboplatin-induced IL-6 and IL-8 production had a significant association with the clinical response to chemotherapy (P=0.016 and P=0.038 respectively). Carboplatin-induced IL-8 overproduction was correlated with FIGO staging III-IV (P=0.026), but no correlation between carboplatin-induced IL-6 and FIGO staging (P= 0.061) was noted. Conclusion: These results suggest that cytokine production in response to platinum-based chemotherapy in primary culture cells may be useful as a predictive marker for the therapeutic outcomes among ovarian or fallopian tube cancer patients.